CHALLENGES AND OPPORTUNITIES OF ONLINE LEARNING IN INDIA - Pallathadka, Harikumar; Kirana Pallathadka, Laxmi (International Journal of Psychosocial Rehabilitation, 2022)
Education is critical for the financial advancement of any country. It assumes an exceptionally vital part in the monetary and social advancement of a country. It advances the usefulness and innovativeness of human resources and makes ready for a business venture and mechanical turn of events. Nations that have utilized human resources to upgrade the utilization of actual capital have accomplished quicker development. Computerized schooling in India was constantly seen as a material advantageous to study hall education.Notwithstanding, the episode of the novel Covid disease has changed the situation of instruction inside and out. The delayed lockdown disrupted the understudy's educational learning activity. A significant part of educational foundations was transferred online to ensure learning coherence. The COVID-19 epidemic has had a devastating impact on all areas of society. It has caused enormous disruption in the educational structure, as governments worldwide have temporarily closed educational institutions to prevent the spread of the Covid. Up close and personal classes have been discontinued and relocated online, resulting in the rise of internet learning, which has enabled students to continue their education. It then discusses significant issues raised by the widespread acceptance of web-based learning amid the epidemic, followed by a discussion of ideas proposed by many specialists to improve the adequacy of online learning. Certain factors, such as insufficient computing foundation, validity, and language used in internet-based training, impede development. With the increase in the number of web users in India, the article also explores future opportunities in education. A sample of 189 respondents was collected through a "standard questionnaire," created on a five-point interval scale.